2016
DOI: 10.1007/s11064-016-1949-2
|View full text |Cite
|
Sign up to set email alerts
|

Naringin and Sertraline Ameliorate Doxorubicin-Induced Behavioral Deficits Through Modulation of Serotonin Level and Mitochondrial Complexes Protection Pathway in Rat Hippocampus

Abstract: The present study was designed to investigate the neuroprotective effect of naringin (NR) alone as well as its combination with sertraline (SRT) against doxorubicin (DOX)-induced neurobehavioral and neurochemical anomalies. DOX (15 mg/kg; i.p.) administration caused behavioral alterations, oxidative stress, neuroinflammation, mitochondrial dysfunction and monoamines alteration in male Wistar rats. NR (50 and 100 mg/kg; i.p.) and SRT (5 mg/kg; i.p.) treatment significantly attenuated DOX-induced anxiety and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 84 publications
4
33
0
1
Order By: Relevance
“…DOX caused increase in corticosterone, as observed in previous studies (de Lima et al, ; Kwatra et al, ; Preziosi, Vacca, Ragazzoni, del Carmine, & Navarra, ). Increased corticosterone levels induce increase in both catabolic pathways (ubiquitin–proteasome and autophagy) in skeletal muscle.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…DOX caused increase in corticosterone, as observed in previous studies (de Lima et al, ; Kwatra et al, ; Preziosi, Vacca, Ragazzoni, del Carmine, & Navarra, ). Increased corticosterone levels induce increase in both catabolic pathways (ubiquitin–proteasome and autophagy) in skeletal muscle.…”
Section: Discussionsupporting
confidence: 85%
“…Other authors have shown similar results, where DOX treatment increased the expression of autophagic proteins and that exercise can negatively regulate them (Campbell & Quadrilatero, 2016;Smuder, Kavazis, Min, & Powers, 2011). DOX-mediated autophagy is caused by increased mitochondrial uncoupling with the elevation of reactive oxygen species (ROS) production, and the exercise is able to increase antioxidant defense, leading to the reduction in ROS generation (Schwalm et al, 2015;Smuder et al, 2011) DOX caused increase in corticosterone, as observed in previous studies Kwatra et al, 2016;Preziosi, Vacca, Ragazzoni, del Carmine, & Navarra, 1989). Increased corticosterone levels induce increase in both catabolic pathways (ubiquitin-proteasome and autophagy) in skeletal muscle.…”
Section: Discussionsupporting
confidence: 76%
“…Neurons in the hippocampus can overdrive DA and 5-HT to distort the emotional change [22,23]. Thus, we detected the levels of these neurotransmitters in the hippocampus by using HPLC.…”
Section: Nko Mice Exhibited Lower Da and Drd1 Levels In The Hippocampusmentioning
confidence: 99%
“…Doxorubicin treatment has been associated with impairments in hippocampal mitochondrial enzyme complexes I and II and with redox activity in rats [49]. Cisplatin treatment was shown to decrease neuronal mitochondrial capacity on the level of spare respiratory capacity [97, 98], which translates to reduced capacity to increase energy production when demand increases.…”
Section: Changes In Cellular Bioenergetics Resulting From Cancer Thermentioning
confidence: 99%
“…Verbal memory performance in survivors was predicted by an interaction between hippocampal volume and TNF-α. Most of the breast cancer survivors in this study (>80%) had received a chemotherapeutic cocktail including doxorubicin, which was shown in an animal model to increase TNF-α (and IL-1β) in the hippocampus [49]. Thus, the association between circulating TNF-α and hippocampal volume found in the clinical study possibly reflects associations between central TNF-α and hippocampal volume, leading to cognitive symptoms.…”
Section: Neuroinflammation and Symptom Experiencementioning
confidence: 88%